Information security awareness through the use of social media - Abdul Molok, Nurul Nuha; Md Ali, Asma; Talib, Shuhaili; Mahmud, Murni (IEEE, 2015)
The proliferation of online social media use amongst employees has been reported to be incriminating organizational information security. Despite the benefits of social media to organizations, there were cases of information leakage, malware, identity theft, espionage and sabotage through such use. This paper explores employees' awareness of information security around social media and presents the initial findings of a study on a tertiary education institution in Malaysia. As an extension to a previous study, this study also found that employees were not only disclosing personal information but they are also disclosing organizational information on social media. This indicates there is a potential for information security threats to organizations through employees' use of social media. Nevertheless, the findings demonstrate that some participants were aware about the implications of employees' use of social media to information security.